Industrial training report: Hotel Seri Malaysia Kepala Batas - Abdull Aziz, Muhammad Haffizi (Universiti Teknologi MARA, Perlis, 2024)
Hotel Seri Malaysia Kepala Batas is one of the Hotel Seri Malaysia chain. It serves mostly services compared to products to the customer which is called guest. They provide variety of room packages which are standard room, family room and two types of suite. In order to make sure achieve customer satisfaction, they give a services like take guest luggage directly to their room, greeting every guest when they come in into the hotel and more. The hotel also offers amenities such as a s restaurant, and meeting facilities for guests to enjoy during their stay. Additionally, Hotel Seri Malaysia Kepala Batas prides itself on its friendly and attentive staff who are always ready to assist guests with any requests or inquiries they may have. To complete my Bachelor’s degree, I am grateful to carry out my internship at Hotel Seri Malaysia Kepala Batas. I gained important hands-on experience and knowledge of the hotel industry. Throughout this time, I was involved in a variety of projects, primarily in the Front Office and Sales Department, where I applied theoretical knowledge to actual settings, developing my technical and analytical skills. Collaborating with a team of experienced experts taught me the value of efficient communication, teamwork, and problem resolution. My supervisors' encouragement and assistance helped me improve professionally, allowing me to successfully navigate and contribute to challenging projects. This internship not only reinforced my awareness of business procedures, but it also highlighted my professional goals, providing me with the confidence and abilities I need for future opportunities.